Leaf expansion and leaf turnover of perennial C4 grasses growing at moderately low temperatures = Expansión y recambio foliar de gramíneas perennes C4 creciendo a temperaturas moderadamente bajas - Berone, German Dario (2016)
Understanding the mechanisms by which some C4 grasses grow more than others at moderately low temperatures (~12-20°C) is valuable to select materials to lengthen the growing season. In turn, the determination of leaf lifespan for each material to be used is relevant to optimize the balance between herbage production and herbage utili zation. The objectives of this study were to analyze the growth capacity and the leaf lifespan in two native materials (Pappophorum caespitosum and Trichloris crinita) and in four materials introduced (Cenchrus ciliaris cv. 'Texas-4464', Cenchrus ciliaris cv. 'Bella', Panicum coloratum cv. 'Klein' and Panicum maximum cv. 'Gatton Panic') commonly used in Argentina. Under non-limiting growth conditions, the rate of leaf appearance and leaf elongation, the number of growing leaves and the leaf lifespan, were measured. The materials showed similar leaf growth capacity through contrasting mechanisms: while three of them (P. coloratum, P. maximum and P. caespitosum) showed higher growth of individual leaves, the rest (C. ciliaris cv. 'Texas-4464', C. ciliaris cv. 'Bella' and T. crinita) showed higher number of growing leaves. The leaf lifespan was not significantly different between materials evaluated. Interestingly, in agreement with previous results obtained in a comparison of C3 grasses, it was observed that materials possessing a greater number of growing leaves had lower values of leaf lifespan. Conocer los mecanismos por los cuales algunas gramíneas C4 crecen más que otras a temperaturas moderadamente bajas (~12-20°C) es valioso para seleccionar materiales que permitan alargar la estación de crecimiento. Por su parte, conocer la vida media foliar de las especies es relevante para optimizar el balance entre producción y utilización de forraje. Los objetivos del trabajo fueron analizar la capacidad de crecimiento y la vida media foliar en dos materiales nativos (Pappophorum caespitosum y Trichloris crinita) y en cuatro materiales introducidos (Cenchrus ciliaris cv. 'Texas-4464', Cenchrus ciliaris cv. 'Bella', Panicum coloratum cv. 'Klein' y Panicum maximum cv. 'Gatton Panic') común mente utilizados en Argentina. Bajo condiciones no limitantes al crecimiento se evaluó la tasa de aparición y elongación foliar, el número de hojas en crecimiento y la vida media foliar. Los materiales tuvieron similar capacidad de crecimiento foliar con mecanismos contrastantes: mientras tres materiales (P. coloratum, P. maximum y P. caespitosum) mostraron mayor crecimiento por hoja, el resto (C. ciliaris cv. 'Texas-4464', C. ciliaris cv. 'Bella' y T. crinita) mostró mayor número de hojas en crecimiento. La vida media foliar no difirió significativamente entre materiales. Interesantemente, y en concordancia con resultados previos de una comparación de gramíneas C3, se observó que los materiales que poseían un mayor número de hojas creciendo simultáneamente tenían menores valores de vida media foliar.